2007
DOI: 10.1016/j.cbpa.2006.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Sex and seasonal co-variation of arginine vasotocin (AVT) and gonadotropin-releasing hormone (GnRH) neurons in the brain of the halfspotted goby

Abstract: Gonadotropin-releasing hormone (GnRH) and arginine vasotocin (AVT) are critical regulators of reproductive behaviors that exhibit tremendous plasticity, but co-variation in discrete GnRH and AVT neuron populations among sex and season are only partially described in fishes. We used immunocytochemistry to examine sexual and temporal variations in neuron number and size in three GnRH and AVT cell groups in relation to reproductive activities in the halfspotted goby (Asterropteryx semipunctata). GnRH-immunoreacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 86 publications
3
47
1
Order By: Relevance
“…Although in L. dimidiatus the size of mPOA neurons did not differ from gPOA AVT-ir, we are highly confident that these are distinct cell populations based on cytoarchitectural and topological criteria. Most studies report a relationship in terms of cell numbers between the three cell groups [pPOA > mPOA > gPOA; Maruska et al, 2007;Dewan et al, 2008;Maruska, 2009], which we did not find. In fact, in L. unilineatus the relationship was exactly the opposite, with the gPOA being the more numerous cell group.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Although in L. dimidiatus the size of mPOA neurons did not differ from gPOA AVT-ir, we are highly confident that these are distinct cell populations based on cytoarchitectural and topological criteria. Most studies report a relationship in terms of cell numbers between the three cell groups [pPOA > mPOA > gPOA; Maruska et al, 2007;Dewan et al, 2008;Maruska, 2009], which we did not find. In fact, in L. unilineatus the relationship was exactly the opposite, with the gPOA being the more numerous cell group.…”
Section: Discussioncontrasting
confidence: 98%
“…After two additional washes the primary AVT antibody was applied in a final dilution of 1: 7,500 (the antibody was diluted with pre-soak solution) and slides were incubated overnight in a sealed humidified chamber at 4 ° C. The antibody used was generously donated by Dr. Matthew Grober (Georgia State University, USA) and has been successfully used in similar studies done with different teleost species [e.g. Maruska et al, 2007;Dewan et al, 2008;Maruska, 2009]. Day 2 started with two washes followed by incubation with the biotinylated goat anti-rabbit secondary antibody (KPL; Kirkegaard & Perry Labs, Inc.) for 30 min, two additional washes and incubation with peroxidase-labelled streptavidin (KPL) for another 30 min.…”
Section: Immunocytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…This result is reminiscent of an earlier study in cricket frogs [ Acris crepitans ;Marler et al, 1999], which found that noncalling satellite males had more AVT staining and larger cells than vigorously calling males in the NAcc population. It is also similar to the results of Maruska et al [2007] who found that AVT cell number and size was higher in female gobies during the nonspawning season compared to the spawning season. It is interesting that in prairie voles, Microtus ochragaster, where male aggression and paternal care are increased by experimentally elevating AVP levels, a decrease in AVP-ir staining (in the lateral septum and the lateral habenular nucleus) is asso-ciated with the expression of these behaviors, whereas staining is greater in control animals that are not behaving [Bamshad et al, 1993[Bamshad et al, , 1994Winslow et al, 1993].…”
Section: Seasonal and Social Changes In Androgens And Avtsupporting
confidence: 90%
“…HPLC measurements of AVT content in salmon neural tissue show AVT levels to be lower in the non-breeding winter period compared to summer [Gozdowska et al, 2006]. Maruska et al [2007] assayed AVT cell number and size and reported instead that both number and size in females, and size in males, was larger in the nonspawning period than the spawning period in halfspotted gobies. In males across many species, brain AVT/AVP levels increase with testosterone [Goodson and Bass, 2001;DeVries and Panzica, 2006;Kabelik et al, 2008], although exceptions can be found [Semsar and Godwin, 2003;Kabelik et al, 2010].…”
Section: Introductionmentioning
confidence: 99%